2019
DOI: 10.1016/j.measurement.2019.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of engine oil aging by diffusion and low-field nuclear magnetic resonance relaxation

Abstract: Time domain, also named lowfield nuclear magnetic resonance is used to monitor oil degradation by measuring relaxation and diffusion. As quality control of oils is indispensable to optimize oil change intervals while simultaneously preventing machinery damage, the technique was applied to detect the degradation state of engine oils as time domain nuclear magnetic resonance is known as a well suited tool to measure quality control parameters for example in food industry. Correlations with commonly applied oil a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 29 publications
0
17
0
2
Order By: Relevance
“…As in any NMR experiment, the repetition time must be adapted to the longitudinal relaxation time T 1 for fastest but still reliable measurements. In other studies, T 1 was found to depend not significantly on aging at Larmor frequencies above 10 MHz, [ 28 ] and saturation recovery experiments were performed on a gear oil and modeled via the gamma distribution function leading to a longitudinal relaxation distribution. [ 29 ] To transfer the experiments to the sensor, a transmission oil was measured in 5 mm NMR tubes undiluted and additionally diluted with deuterated chloroform (2:1, 99.8%) for showing the feasibility (Figure 4).…”
Section: Application To the Study Of Lubricantsmentioning
confidence: 99%
See 3 more Smart Citations
“…As in any NMR experiment, the repetition time must be adapted to the longitudinal relaxation time T 1 for fastest but still reliable measurements. In other studies, T 1 was found to depend not significantly on aging at Larmor frequencies above 10 MHz, [ 28 ] and saturation recovery experiments were performed on a gear oil and modeled via the gamma distribution function leading to a longitudinal relaxation distribution. [ 29 ] To transfer the experiments to the sensor, a transmission oil was measured in 5 mm NMR tubes undiluted and additionally diluted with deuterated chloroform (2:1, 99.8%) for showing the feasibility (Figure 4).…”
Section: Application To the Study Of Lubricantsmentioning
confidence: 99%
“…Modeling of magnetization decays by gamma distributions [ 30 ] was shown to describe the magnetization decays of lubricating oils to a high level of numerical accuracy. [ 28,29 ] In the present case, an extension is needed. The noise level here typically amounts to about 0.3% of the maximum signal intensity for 64 acquisitions.…”
Section: Application To the Study Of Lubricantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Summarizing, particulate contamination in oils can be detected by NMR via susceptibility differences (line width or magnetic resonance imaging) or geometrical hindrance (PFG‐NMR). Particles in the small nanometer range and paramagnetic ions cause additionally measurable paramagnetic relaxation enhancement (PRE) …”
Section: Lf‐nmr In Oil Production Formulation and Usementioning
confidence: 99%